STUDY AND ANALYSIS OF THE EFFECT OF THE CHARGE INITIATION METHOD ON STEMMING MOVEMENT IN A BLAST HOLE - Mardanov I. N. (Journal Park Publishing, 2026)
A review of literary sources is presented, reflecting the efficiency and necessity of using stemming in blast holes during the explosive fragmentation of rocks, as well as the influence of the charge initiation method on rock fragmentation.
Keywords: Blast hole, stemming, rocks, explosive, stemming length, line of least resistance, charge initiation, rock fragmentation.